Living myocardial slices for the study of nucleic acid-based therapies - Nunez-Toldra, R.; Del Canizo, A.; Secco, I.; Nicastro, L.; Giacca, M.; Terracciano, C. M. (Frontiers in Bioengineering and Biotechnology, 2023)
Gene therapy based on viral vectors offers great potential for the study and the treatment of cardiac diseases. Here we explore the use of Living Myocardial Slices (LMS) as a platform for nucleic acid-based therapies. Rat LMS and Adeno-Associated viruses (AAV) were used to optimise and analyse gene transfer efficiency, viability, tissue functionality, and cell tropism in cardiac tissue. Human cardiac tissue from failing (dilated cardiomyopathy) hearts was also used to validate the model in a more translational setting. LMS were cultured at physiological sarcomere length for 72-h under electrical stimulation. Two recombinant AAV serotypes (AAV6 and AAV9) at different multiplicity of infection (MOI) expressing enhanced green fluorescent protein (eGFP) were added to the surface of rat LMS. AAV6 at 20,000 MOI proved to be the most suitable serotype without affecting LMS contractility or kinetics and showing high transduction and penetrability efficiency in rat LMS. This serotype exhibited 40% of transduction efficiency in cardiomyocytes and stromal cells while 20% of the endothelial cells were transduced. With great translational relevance, this protocol introduces the use of LMS as a model for nucleic acid-based therapies, allowing the acceleration of preclinical studies for cardiac diseases.